2013
DOI: 10.1016/j.hlc.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Morphology and Function in Chronic Obstructive Pulmonary Disease Patients Living at High Altitude

Abstract: An increase in mean pulmonary artery pressure and right ventricular dimensions are observed in COPD patients living at high altitude. Despite this increase, systolic and diastolic functions of the right ventricle, as well as global right ventricular performance are similar in COPD patients living at high altitude and sea level. Altitude-related adaptation to chronic hypoxia could explain these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…These results are in accordance with data published by Güvenç et al [31] describing larger enddiastolic and end-systolic RV diameters and end-systolic areas as well as reduced FAC in patients with COPD liv- ing at moderate altitude. As in our study collective, Gü-venç et al [31] could not detect any difference in TAPSE when comparing patients with COPD living at sea level with those living at moderate altitude, which might indicate that impairments of RV function are only mild, mainly driven by an increased volume and an only minor reduction in contractility.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in accordance with data published by Güvenç et al [31] describing larger enddiastolic and end-systolic RV diameters and end-systolic areas as well as reduced FAC in patients with COPD liv- ing at moderate altitude. As in our study collective, Gü-venç et al [31] could not detect any difference in TAPSE when comparing patients with COPD living at sea level with those living at moderate altitude, which might indicate that impairments of RV function are only mild, mainly driven by an increased volume and an only minor reduction in contractility.…”
Section: Discussionsupporting
confidence: 93%
“…It remains unclear if increases in PAP may be attributed to diastolic dysfunction or vice versa. The previously mentioned study by Güvenç et al [31] found no significant difference in mitral E or A wave between patients with COPD living at sea level and those living at moderate altitude (1,768 m). A partial influence of impaired LV diastolic function on increases in PAP cannot be completely dismissed, even though an association was not found in our regression analysis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Despite this increase, systolic and diastolic functions of the RV, as well as global RV performance were similar in COPD patients living at high altitude and sea level, suggesting an adaptation to chronic hypoxia in those patients [ 23 ].…”
Section: Patients With Pre-existing Diseases: Copd Myocardial Infarcmentioning
confidence: 88%
“…Although limited field studies have been performed, one study in 1978 showed that resting PaO2 dropped to just 51.2mmHg within 3hrs of arriving at 1920m altitude, and PaO2 universally dropped below 6.7 during light exercise in a more recent chamber study with a simulated altitude of 2438m (66,67). Mean pulmonary artery pressure was significantly higher in COPD patients resident at an altitude of 1768m compared to sea level (36.05mmHg vs 26.78mmHg, p<0.001) (68). Importantly, treatment of other altitude illness may also compound underlying COPD.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%